Adventure time. The complete fourth season [videorecording (DVD)] - Shada, Jeremy ([publisher not identified], 2014)
It's one crazy adventure after another for human boy Finn and his best friend, Jake, a 28-year-old dog with magical powers. They're out to have the most fun possible and they sure do find it exploring the Land of Ooo! Whether it's saving Princess Bubblegun, battling zombie candy, taunting the Ice King, or rocking out with Marceline the Vampire Queen, with Finn and Jake it's always an adventure.